Helminth parasites from Red Sea fishes: Neowardula brayi gen. nov., sp. nov. (Trematoda: Mesometridae Poche, 1926) and Sclerocollum saudii sp. nov. (Acanthocephala: Cavisomidae Meyer, 1932) - Al-Jahdali, Mohammed O. (Zootaxa, 2010)
Specimens of the fishes Acanthopagrus bifasciatus Forsskål (Sparidae) and Siganus rivulatus Forsskål (Siganidae) were caught in the Red Sea off the coast of Rabigh, Saudi Arabia. Four (25%) and 24 (80%) of these fishes, respectively, were found to harbour intestinal helminths. Acanthopagrus bifasciatus was parasitised by Neowardula brayi gen. nov., sp. nov. (Trematoda: Mesometridae) and S. rivulatus by Sclerocollum saudii sp. nov. (Acanthocephala: Cavisomidae). Neowardula brayi gen. nov. is similar to Wardula Poche, 1926, but clearly differs from it and from the other four genera of the family Mesometridae Poche, 1926 in having a ventral surface anterior to the intestinal bifurcation greatly modified into a well-developed, relatively deep pouch encircling the genital pore and constantly diagonal testes. Sclerocollum saudii sp. nov. is similar to S. rubrimaris Schmidt et Paprena, 1978 (type species), but clearly differs in having a proboscis only armed with 10 rows of hooks, smaller proboscis hooks, lemnisci much longer than proboscis receptacle and much smaller egg size. The developmental stages of this acanthocephalan (cystacanths, juveniles and immature worms) are also described and figured.